Implementing sustainability in teaching: The role of sustainability leadership and transformational leadership in the context of higher education institutions - Jo\~ao Henrique Paulino Pires Eustachio; Walter Leal Filho; Amanda Lange Salvia; Yana Medeiros Guimar\~aes; Luciana L. Brandli; Laís Viera Trevisan; Jelena Barbir; Adriana Cristina Ferreira Caldana (Sustainable Development, 2024)
This paper aims to explore the mechanism by which sustainability leadership (SL) and transformational leadership (TL) contribute to implementing sustainability-related aspects and the adoption of the SDGs by the teaching staff and whether these relationships are mediated by the higher education institutions' (HEIs) level of social innovation tendency. The authors relied on a world survey containing questions developed according to the literature to achieve the results, receiving 603 answers from teaching staff in 102 developed and developing countries. To analyse the data, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were deployed to check the instruments and the model's structure of factors, and structural equation modelling with hypotheses testing was adopted to understand the level of significance and the magnitude of the relationship between the constructs. The results indicate that SL has a significantly strong relationship with TL, social innovation tendency, and the adoption of sustainability aspects in teaching; however, it is not possible to support the existence of a significant relationship between TL and the adoption of sustainability aspects in teaching, and between social innovation tendency and the adoption of sustainability aspects in teaching. Theoretical and practical implications are explored.
Keywords: 330; education for sustainable development; higher education institutions; social innovation; sustainability leadership; transformational leadership